2014
DOI: 10.1530/eje-13-0924
|View full text |Cite
|
Sign up to set email alerts
|

Patients lost to follow-up in acromegaly: results of the ACROSPECT study

Abstract: Objective: The complex management of acromegaly has transformed this disease into a chronic condition, with the risk of patients being lost to follow-up. The objective of this study was to estimate the proportion of acromegalic patients lost to follow-up in France and to determine the impact that abandoning follow-up has on the disease and its management. Design: ACROSPECT was a French national, multicentre, cross-sectional, observational study. Methods: Acromegalic patients were considered lost to follow-up i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Previous studies show that a significant proportion of young people with CCCs experience care gaps, and some are even completely lost to follow-up. [16][17][18][19][20][21] Improving continuity of care for young people with CCCs requires tailored interventions or strategies to facilitate a smooth and continuous care process. An in-depth understanding of determinants of care gaps is, nevertheless, indispensable for developing such interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies show that a significant proportion of young people with CCCs experience care gaps, and some are even completely lost to follow-up. [16][17][18][19][20][21] Improving continuity of care for young people with CCCs requires tailored interventions or strategies to facilitate a smooth and continuous care process. An in-depth understanding of determinants of care gaps is, nevertheless, indispensable for developing such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 This health care transition is an important but challenging life event, 14 and successful transfer to adult care is paramount for young people with CCCs. 15 Gaps in this transitional process occur in 7% to 21% of young people with acromegaly, [16][17][18] 9% to 17% of HIV-infected adolescents, 19 11% to 24% of patients with type I diabetes mellitus, 20 and 7% to 76% of young people with congenital heart disease. 21 This break in the delivery of health care (ie, care gaps) as adolescent patients leave pediatric care is associated with increased morbidity rates, longterm complications, number of hospitalizations, need for urgent interventions or reinterventions, and higher rates of health-risk behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding treatment adherence and outcomes specific to acromegaly are scarce, although one registry study reported that nonadherence accounted for ~20% of patients with uncontrolled disease 22. There is also evidence suggesting a need for improved adherence to follow-up and monitoring;23 patients may not be aware of the need for follow-up24 or may think treatment and/or follow-up are unnecessary due to an absence of subjective symptoms,16 and the inability to closely monitor patients seems to be associated with a lower rate of treatment and high rate of active disease 16,23,24. From a broader perspective, an association between adherence to therapy and treatment outcomes has been demonstrated in multiple disease states, including chronic diseases,2531 suggesting the same would be true in acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher rates of active disease have been reported in a small study in patients with suboptimal monitoring who were lost to follow-up (20) . Similarly, in a large cohort study, a proportion of patients lost to follow-up had not received optimal monitoring and follow-up care (21) . The lack of monitoring can have deleterious long-term consequences due to continued exposure to elevated levels of GH and IGF1.…”
Section: Introductionmentioning
confidence: 99%